The emerging role for metabolism in fueling neutrophilic inflammation. Issue 1 (3rd November 2022) - Morrison, Tyler; Watts, Emily R.; Sadiku, Pranvera; Walmsley, Sarah R.
Summary: Neutrophils are a critical element of host defense and are rapidly recruited to inflammatory sites. Such sites are frequently limited in oxygen and/or nutrient availability, presenting a metabolic challenge for infiltrating cells. Long believed to be uniquely dependent on glycolysis, it is now clear that neutrophils possess far greater metabolic plasticity than previously thought, with the capacity to generate energy stores and utilize extracellular proteins to fuel central carbon metabolism and biosynthetic activity. Out‐with cellular energetics, metabolic programs have also been implicated in the production of neutrophils and their progenitors in the bone marrow compartment, activation of neutrophil antimicrobial responses, inflammatory and cell survival signaling cascades, and training of the innate immune response. Thus, understanding the mechanisms by which metabolic processes sustain changes in neutrophil effector functions and how these are subverted in disease states provides exciting new avenues for the treatment of dysfunctional neutrophilic inflammation which are lacking in clinical practice to date.